THE IMPORTANCE OF THE BOOK IN THE DEVELOPMENT OF HUMAN THINKING, PHYSICAL, MENTAL AND SPIRITUAL HEALTH. (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
People today are very busy and rarely spare time for reading. Because it is easier to immerse yourself in virtual life and have fun by grabbing the TV remote control, turning on the smartphone or opening the notebook.However, people who read books have a higher chance of building a successful career, improving family relationships, they look younger than others and live longer. Therefore, I would recommend reading books for young people to spend their free time meaningfully.